PENGGUNAAN STRATEGI GUIDE NOTE TAKING BERBANTUAN VIDEO ANIMASI MOTION GRAPHIC PADA MATERI IPA DI SDN 12 PONTIANAK TIMUR - Ajie, Rizky Julianto; Setyaningrum, Vidya; Wahab, Wahab (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2023)
This research is motivated by the low learning outcomes of students and teachers who still use lecture and question-and-answer learning methods in science learning class 4 SDN 12 Pontianak Timur. The purpose of this study was to analyze the learning outcomes of students at the beginning, end, and how the effect of the guide note-taking strategy assisted by motion graphic animation video media. The method used is a quantitative experiment with the design "nonequivalent control group design". The population in this study were all grade 4 students of State Elementary School 12 East Pontianak. The samples in this study were class 4A as the control class and class 4B as the experimental class. Data was collected using observation sheets, test sheets and documentation. The average result of the control class pretest was 67.976, while the experimental class was 75.35. While the control class post-test was 76.68, and the experimental class was 89.59. Based on the results of hypothesis testing using SPSS, the value (sig) of 0.004 <0.05 was obtained. Indicates there is a difference in average between research samples. Based on the processed effect size results, it is known that the Cohen's d effect size value of 0.60 is included in the medium criteria. So it can be concluded that there is an effect of the guide note-taking strategy assisted by motion graphic animation video media on student learning outcomes, namely 0.60 with a moderate category.